2015
DOI: 10.1080/0309877x.2015.1070399
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social norms of health behaviours and college engagement in British students

Abstract: Community Engagement ManagerTech Stories * Corresponding author 2 Perceived social norms of health behaviours and college engagement in British students Abstract AimsThe social norms approach is an increasingly widely used strategy of behaviour and attitude change that is based on challenging misperceptions individuals hold about their peers. Research to date has been carried out predominately in the American college system, with a focus on substance use behaviours. The aim of the current study was to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Overestimations of social norms have been evidenced for drinking sugar-sweetened beverages ( Perkins J.M. et al, 2010 ; Lally et al, 2011 ), eating unhealthy snacks ( Lally et al, 2011 ), using ‘smart drugs’ to improve academic performance at university ( Helmer et al, 2016b ), using non-medically prescribed sedatives and sleeping pills ( Lehne et al, 2018 ), engaging in distracted driving behavior ( Carter et al, 2014 ), risky sexual behaviors ( Lewis et al, 2007 ; McAlaney and Jenkins, 2017 ), as well as overestimating the rates of sexually transmitted infections and unintended pregnancies amongst peers ( Scholly et al, 2005 ). Misperceived social norms can influence perceptions of what is considered to be a healthy or attractive body image, such as misperceptions of peer desirability of thinness and muscularity ( Grossbard et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overestimations of social norms have been evidenced for drinking sugar-sweetened beverages ( Perkins J.M. et al, 2010 ; Lally et al, 2011 ), eating unhealthy snacks ( Lally et al, 2011 ), using ‘smart drugs’ to improve academic performance at university ( Helmer et al, 2016b ), using non-medically prescribed sedatives and sleeping pills ( Lehne et al, 2018 ), engaging in distracted driving behavior ( Carter et al, 2014 ), risky sexual behaviors ( Lewis et al, 2007 ; McAlaney and Jenkins, 2017 ), as well as overestimating the rates of sexually transmitted infections and unintended pregnancies amongst peers ( Scholly et al, 2005 ). Misperceived social norms can influence perceptions of what is considered to be a healthy or attractive body image, such as misperceptions of peer desirability of thinness and muscularity ( Grossbard et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first “social norms interventions” were originally used to reduce alcohol consumption in a few US universities in the early 1980s by correcting students’ overestimates of how much other students drink [ 24 ]. Later, more campuses (mostly in the US, Canada, and the UK) used similar interventions to address tobacco use [ 25 ], sexual violence [ 26 , 27 ], and use of recreational drugs [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though empirical findings in the health sciences have offered ground-breaking contributions to our understanding of the influence of social norms on a wide range of health outcomes (e.g. Piliavin and Libby, 1986;Peterson et al, 2009;Gidycz et al, 2011;McAlaney and Jenkins, 2015;Berger and Caravita, 2016;Prestwich et al, 2016;Templeton et al, 2016), most of these empirical findings emerge from studies conducted in highincome countries; the most famous case being the use of social norms theory to reduce use of alcohol and recreational drugs in US college campuses (Borsari and Carey, 2003; Lewis and Neighbors, 2006;Prestwich et al, 2016). This narrow evidence base is particularly problematic given donors' and practitioners' recent interest in integrating social norms theory into health interventions in LMIC.…”
Section: Social Norms and Health Interventions In Lmicmentioning
confidence: 99%
“…Contemporary research in health science has empirically demonstrated the usefulness of the third, 'norms as beliefs', school of thought, which emerged mostly from social psychology (e.g. Cialdini et al, 1990), as a means to explain and also to influence people's health-related choices (Borsari and Carey, 2003;Eisenberg et al, 2005;Rimal and Real, 2005;McAlaney and Jenkins, 2015;Ahmed et al, 2016). Contemporary scholars in this tradition argue that social norms are one's beliefs about (i) what others do and (ii) of what others approve and disapprove of (Gibbs, 1965;Cialdini et al, 1991;Cialdini and Trost, 1998;Lapinski and Rimal, 2005;Bicchieri, 2006; for a full review see Mackie et al, 2015).…”
Section: Social Norms and Health Interventions In Lmicmentioning
confidence: 99%